Relationship of Antenatal Care Visits Viewed from the Standards of Antenatal Care Visits with Pregnancy Risks in the Work Area of Tanjung Bingkung Health Center, Solok District - Fransisca, Dewi; Darma, Ika Yulia; Fernando, Fenny; Pebrina, Melia; Hayu, Ramah; Mavelya, Whike (PT. Riset Press International, 2025)
The Tanjung Bingkung Health Center ranks first in the number of high-risk pregnant mothers and has the lowest K6 in Solok District, with 78 high-risk pregnant mothers recorded in July 2023 out of a target of 72. Additionally, the number of high-risk pregnant mothers has increased over the last three years. This study aims to determine the relationship between antenatal care visits, assessed according to antenatal care visit standards, and pregnancy risks in the working area of Tanjung Bingkung Health Center, Solok District, in 2023. This is an analytical study with a cross-sectional design. The population includes all third-trimester pregnant women with a gestational age above 36 weeks from November to December 2023, totaling 40 individuals. The sampling technique used is total sampling, and data collection tools include a questionnaire and KIA (Maternal and Child Health) book. Data analysis was conducted univariately and bivariately using SPSS with the Chi-square statistical test. The results showed that 11 respondents (27.5%) had antenatal care visits that did not meet standards, and 15 individuals (37.5%) were at risk during pregnancy. Among the 11 pregnant women with non-standard antenatal care visits, the majority, 8 (72.7%), were classified as having high-risk pregnancies, with a p-value of 0.009. There is a significant relationship between antenatal care visits, as viewed from the standards of antenatal care visits, and pregnancy risks in the working area of Tanjung Bingkung Health Center, Solok District, in 2023. To reduce the high rate of pregnancy risks, it is hoped that all pregnant women will attend ANC visits according to the standards.